Women's know-how comes together - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
Gendered Worlds: Gains and Challenges is the theme of the Women s Worlds 2002 Congress to be held in Kampala from 21 to 26 July, 2002. Sessions include agriculture, environment and water management.Department of Women and Gender StudiesMakerere...